Influence of Service Integrity on Customer Retention in Kenya’s Coastal Hotels - Achieng, Sylvia A.; Pepela, Anthony W. (Current Topics on Business, Economics and Finance Vol. 6, 2023)
This study seeks to establish whether there is a relationship between service integrity and customer retention in classified hotels in Kenya’s coastal tourism hub. It targets hotel customers of the 15 classified hotels in Kenya’s Mombasa County, based on a descriptive research design. A stratified sampling technique is adopted where three strata based on the hotels’ star-rating are formed to cover 384 customers, 26 for each of the hotels. A questionnaire is developed for data collection. Kenya’s coastal region, a rich tourist hub endowed with world renowned pristine beaches, tourist sites and classified hotels has been facing a slump partly occasioned by insecurity in the region, seasonality challenges and constant travel advisories. This is despite the hotel industry’s phenomenal growth globally. While other tourism destinations affected by calamities are highly resilient to such shocks, thanks to their innovative management strategists that enhance customer retention, it is not clear whether the same applies to Kenya’s coastal tourism hub. The results of this study are significant to hotel practitioners and policy-makers as it will help them re-invent their customer service integrity strategies so as to maximise on customer retention, hence boost hotel performance. Though studies on customer retention have been curried out, there is little empirical evidence suggesting the use of service integrity.